PER Indicators and Sustainability in Implanted Forests Regulation in Argentina - Minaverry, Clara María (2018)
This paper is focused on the regulation and institutional development contrasts of planted forests at Northeast, Northwest and New Cuyo regions in Argentina, taking into consideration «traditional» and «extended» environmental sustainability principle parameters. It is important to add that this principle was highly exceeded by other environmental management paradigms, but they are not suitable to be applied to implanted forests regulations in Argentina. Also, it refers to the contribution provided by legal international instruments and regional regulations. One of the most original approaches of this research is that PER indicators (Pressure, Condition and Response) were applied and adjusted to the legal arena. Finally we can state that planted forests regulations focuses on a limited horizon of production maximization, highlighting economic and forests commercial activties.